Household antibiotic use in Malawi: A cross-sectional survey from urban and peri-urban Blantyre. - Eleanor E MacPherson; John Mankhomwa; Justin Dixon; Raymond Pongolani; Mackwellings Phiri; Nicholas Feasey; Thomasena O'Byrne; Rachel Tolhurst; Peter MacPherson (PLOS Global Public Health)
Antimicrobial resistance (AMR) is a significant threat to public health. Use of antibiotics, particularly in contexts where weaker regulatory frameworks make informal access easier, has been identified as an important driver of AMR. However, knowledge is limited about the ways antibiotics are used in communities in Malawi and sub-Saharan Africa. Between April and July 2021, we undertook a cross-sectional survey of community antibiotic use practices in Blantyre, Malawi. We selected two densely-populated neighbourhoods (Chilomoni and Ndirande) and one peri-urban neighbourhood (Chileka) and undertook detailed interviews to assess current and recent antibiotic use, supported by the innovative "drug bag" methodology. Regression modelling investigated associations with patterns of antibiotic recognition. We interviewed 217 households with a total of 1051 household members. The number of antibiotics recognised was significantly lower among people with poorer formal health care access (people with unknown HIV status vs. HIV-negative, adjusted odds ratio [aOR]: 0.76, 95% CI: 0.77-.099) and amongst men (aOR: 0.83, 95% CI: 0.69-0.99), who are less likely to support healthcare-seeking for family members. Reported antibiotic use was mostly limited to a small number of antibiotics (amoxicillin, erythromycin and cotrimoxazole), with current antibiotic use reported by 67/1051 (6.4%) and recent use (last 6 months) by 440/1051 (41.9%). Our findings support the need for improved access to quality healthcare in urban and peri-urban African settings to promote appropriate antibiotic use and limit the development and spread of AMR.